Martensitic free-cutting stainless steel rod-shaped steel material and method for producing same
By controlling the microstructure of Cr carbide and sulfide in high hardness/high corrosion resistance Martensite, the problems of tool wear and chip accumulation during cutting processing are solved, and excellent tool life and smooth surface are achieved, suitable for high hardness precision components.
Patent Information
- Application Number
- CN202380058135.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-26
- Filing Date
- 2023-08-29
- Publication Date
- 2025-03-18
AI Technical Summary
The prior art is difficult to suppress tool wear during cutting processing in high hardness/high corrosion resistance Martensite stainless steel, and takes into account excellent tool life and smooth cutting surface.
By controlling the average equivalent circle diameter and number density of Cr carbide, the tool life during precision cutting is excellent; at the same time, by controlling the average equivalent circle diameter and number density of sulfide, the formation of accumulated chip marks is suppressed, and surface properties with excellent smoothness are obtained.
It realizes that in high hardness/high corrosion resistance Martensite stainless steel, it has excellent tool life and excellent cutting surface properties during cutting processing, and is suitable for precision components with excellent hardness/corrosion resistance.
Smart Images

Figure BDA0005262949030000111 
Figure BDA0005262949030000121 
Figure BDA0005262949030000131
Abstract
Description
Technical Field
[0001] The present invention relates to a material to be cut into small parts requiring corrosion resistance, and to a martensitic free-cutting stainless steel bar material having excellent machinability with suppressed tool wear and built-up edge, and a method for producing the same. Background Art
[0002] High hardness / high corrosion resistance martensitic stainless steel of 400 Hv or above is used in industrial instruments and precision instrument parts from the viewpoint of wear resistance, fatigue strength and corrosion resistance. In particular, precision instrument parts that are cut by grinding rods using rods and wires as raw materials are mostly used in rotating bodies, so precise cutting processability is particularly required. Specifically, the tool wear during cutting is required to be as small as less than 200 μm, and a smooth cutting surface is required to be observed to the extent that tiny built-up edges are sparsely observed after cutting. Tool wear is promoted by hard precipitates or inclusions present in the cut material. Built-up edge is a deposit generated and grown by the bonding of the base material to the front end of the cutting tool. It falls off from the front end of the tool during the cutting process and is pressed onto the cutting surface, which deteriorates the cutting surface properties.
[0003] So far, there has been a proposal for a martensitic free-cutting stainless steel as follows: S is added to a high-hardness / high-corrosion-resistant martensitic stainless steel, and the sulfide composition / size and carbide size are specified to improve wear resistance and cutting performance (Patent Document 1). However, this proposal only considers the 10 μm 2 The above very large carbide sizes cannot fully meet the requirements of cutting tool life and cutting surface properties.
[0004] Furthermore, a steel is proposed, which is a cold tool steel with high cold workability, wherein the average equivalent circle diameter of carbides and the cleanliness of inclusions are specified to improve cold workability and machinability (Patent Document 2). However, it is the following proposal: by setting the average equivalent circle diameter of carbides to 0.25μm to 0.8μm, the machinability and cold workability are improved by using low hardness. There is no description of the fact that coarse carbides with an average equivalent circle diameter of carbides exceeding 0.8μm promote tool wear and deteriorate machinability. When the average equivalent circle diameter of carbides is less than 0.25μm, it is considered that the hardness is high and the effect of improving machinability cannot be obtained. In addition, there is no description of the cutting surface properties.
[0005] Furthermore, a steel has been proposed which is a martensitic stainless free-cutting steel containing S, wherein B and N are contained and the size of the BN-based intermetallic compound is specified; or the formation of built-up edge is suppressed by reducing the aspect ratio of inclusions in the steel, thereby improving the surface properties (Patent Documents 3 and 4). However, no description is given about tool life.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2015-137381
[0009] Patent Document 2: Japanese Patent Application Publication No. 2006-193790
[0010] Patent Document 3: Japanese Patent Application Publication No. 2013-185195
[0011] Patent Document 4: International Publication No. WO2019 / 240209 Summary of the invention
[0012] Problems to be solved by the invention
[0013] The inventors of the present invention have recognized that, with respect to the known technologies described in the above-mentioned background art or their combination, it is not possible to achieve an excellent tool life in which tool wear during cutting is suppressed to 200 μm or less in a high hardness / high corrosion-resistant martensitic free-cutting stainless steel having excellent machinability, and further, it is not possible to achieve both a tool life and an excellent smooth surface property in which built-up edge marks are suppressed.
[0014] The problem to be solved by the present invention is to provide a high hardness / high corrosion resistance martensitic free-cutting stainless steel bar material and a method for manufacturing the same, which has excellent tool life during cutting for precision parts of martensitic stainless steel used in a severely corrosive environment and which can obtain a cutting surface property with excellent flatness through cutting.
[0015] Means for solving problems
[0016] In order to solve the above problems, the inventors of the present invention have conducted various studies on a martensitic free-cutting stainless steel containing S that can obtain a high hardness of 400 Hv or more during quenching. As a result, they have found that by controlling the average equivalent circle diameter and number density of Cr carbides, the tool life during precision cutting is excellent, and more preferably, by controlling the average equivalent circle diameter and number density of sulfides, built-up edge is suppressed and a surface property excellent in smoothness can be obtained.
[0017] The present invention has been made based on the above-mentioned findings, and the gist of the present invention is as follows.
[0018] [1] A martensitic free-cutting stainless steel bar material, characterized in that it has the following chemical composition: in terms of mass %, C: 0.10-0.60%, Si: 0.1-2.0%, Mn: 0.1-3.0%, S: 0.15-0.40%, P: 0.10% or less, Cr: 11.0-16.0%, and the remainder includes Fe and impurities.
[0019] The average Cr carbide equivalent circle diameter is less than 0.80μm, and the number density of Cr carbides is 0.10 / μm 2 above.
[0020] [2] A martensitic free-cutting stainless steel bar material, characterized in that it has the following chemical composition: in terms of mass %, C: 0.10-0.60%, Si: 0.1-2.0%, Mn: 0.1-3.0%, S: 0.15-0.40%, P: 0.10% or less, Cr: 11.0-16.0%, and the remainder includes Fe and impurities.
[0021] The average Cr carbide equivalent circle diameter is less than 0.80μm, and the number density of Cr carbides is 0.10 / μm 2 The average sulfide equivalent circle diameter is less than 5.0 μm, and the sulfide number density is 0.010 pieces / μm 2 above.
[0022] [3] The martensitic free-cutting stainless steel bar according to [1] or [2], characterized in that the chemical composition of the steel contains, in mass%, one or more selected from the group consisting of B: 0.01% or less, N: 0.15% or less, Al: 0.008% or less, O: 0.015% or less, Ni: 1.5% or less, Cu: 1.5% or less, Co: 1.5% or less, Mo: 2.5% or less, W: 2.5% or less, Bi: 0.2% or less, Sn: 0.3% or less, Sb: 0.3% or less, Ag: 0.3% or less, Te: 0.1% or less, V: 0.8% or less, Nb: 0.3% or less, Ti: 0.3% or less, Ta: 0.3% or less, Mg: 0.01% or less, Ca: 0.01% or less, Hf: 0.01% or less, and REM: 0.05% or less, in place of a portion of the Fe.
[0023] [4] The method for producing a martensitic free-cutting stainless steel bar according to [1] or [2], characterized in that the finishing temperature of the hot working is 800 to 1150°C, and after the hot working, intermittent annealing is performed by maintaining the temperature at 700 to 900°C for 60 to 300 minutes and cooling to 600°C at a rate of 20 to 200°C / h, or in addition to the intermittent annealing, strand annealing is performed by maintaining the temperature at 700 to 850°C for 30 to 1000 seconds.
[0024] [5] The method for producing a martensitic free-machining stainless steel rod according to [4], characterized in that cold working is further performed with a reduction of area of 20.0 to 99.0%.
[0025] [6] The method for producing a martensitic free-cutting stainless steel bar according to [3], characterized in that the finishing temperature of hot working is 800-1150°C, and after hot working, intermittent annealing is performed by maintaining the temperature at 700-900°C for 60-300 minutes and cooling to 600°C at a rate of 20-200°C / h, or wire annealing is performed on the basis of the above intermittent annealing by maintaining the temperature at 700-850°C for 30-1000 seconds.
[0026] [7] The method for producing a martensitic free-cutting stainless steel rod according to [6], characterized in that cold working is further performed with a reduction of area of 20.0 to 99.0%.
[0027] According to the present invention, a material and a method for manufacturing the material are provided which can obtain a good cutting tool life in a martensitic free-cutting stainless steel rod material, and can further obtain an excellent flat cutting surface property with suppressed built-up edge, and is suitable for high hardness / excellent corrosion resistance precision parts. DETAILED DESCRIPTION
[0028] The requirements of the present invention are described below. It should be noted that (%) in the following description refers to mass (%) unless otherwise specified.
[0029] 《Required Elements》
[0030] In the present invention, the target is a member having a hardness of 400 Hv or more for which wear resistance is generally effective, and a high hardness martensitic free-machining stainless steel having a hardness of at least 400 Hv or more in a quenched state is used as a basis.
[0031] Regarding C, in order to set the hardness of the base material after quenching to 400 Hv or more, C is contained at 0.10% or more. However, if C is contained at more than 0.60%, the average Cr carbide equivalent circle diameter exceeds 0.8 μm, and the cutting tool life is deteriorated. Therefore, the C content is limited to less than 0.60%. The range of 0.20 to 0.50% is preferred.
[0032] Regarding Si, in order to deoxidize and suppress the formation of coarse inclusions that deteriorate the life of the cutting tool, Si is contained at 0.1% or more. However, if Si is contained in excess of 2.0%, hardening occurs, thereby deteriorating the life of the cutting tool, and the bonding of the base material to the tool is promoted, thereby promoting the formation of built-up edge marks. Therefore, the Si content is limited to 2.0% or less. The preferred range is 0.2 to 1.0%.
[0033] Regarding Mn, in order to deoxidize and suppress the formation of coarse inclusions that deteriorate the life of the cutting tool, and to form sulfides to ensure good cutting surface properties, Mn is contained at 0.1% or more. However, if Mn is contained at more than 3.0%, hardening occurs, thereby deteriorating the cutting tool life, and the average sulfide equivalent circle diameter exceeds 5μm, deteriorating the cutting surface properties. Therefore, the Mn content is limited to 3.0% or less. It is preferably in the range of 0.2 to 2.0%.
[0034] Regarding S, in order to form sulfides to ensure good cutting tool life and cutting surface properties, S is contained in an amount of 0.15% or more. However, if S is contained in an amount exceeding 0.40%, hardening occurs, thereby deteriorating the cutting tool life, and the average sulfide equivalent circle diameter exceeds 5 μm, deteriorating the cutting surface properties. Therefore, the S content is limited to 0.40% or less. The range of 0.17 to 0.35% is preferred.
[0035] P is mixed in from the raw materials as an inevitable impurity, but if it is contained in excess of 0.10%, not only will the corrosion resistance be deteriorated due to grain boundary segregation, but the manufacturability will also be significantly reduced. Therefore, the P content is limited to 0.10% or less, preferably 0.05% or less.
[0036] Cr is a basic element for obtaining the corrosion resistance of stainless steel, and is contained at 11.0% or more. However, if Cr is contained at more than 16.0%, the hardness during quenching cannot be ensured to be more than 400 Hv. Therefore, the Cr content is limited to 16.0% or less. Preferably, it is 11.5 to 15.0%.
[0037] 《Equivalent circle diameter and number density of Cr carbides, equivalent circle diameter and number density of sulfides》
[0038] Cr carbides have very high hardness, so they cause abrasive wear on the tool during cutting, which reduces the tool life. The coarser the Cr carbides are and the lower their number density is, the more significant their impact becomes. Therefore, the average Cr carbide equivalent circle diameter is limited to less than 0.80 μm, and the Cr carbide number density is limited to 0.10 pieces / μm. 2 Preferably, the average Cr carbide equivalent circle diameter is 0.70 μm or less, and the Cr carbide number density is 0.20 pieces / μm 2 above.
[0039] Sulfides serve as the starting point for cutting chips during cutting, and are effective in suppressing the formation of built-up edge and obtaining good surface properties. The finer the sulfides and the higher their number density, the more significant their influence becomes. Therefore, it is preferred to limit the average sulfide equivalent circle diameter to 5.0 μm or less and the sulfide number density to 0.010 pieces / μm. 2 More preferably, the average sulfide equivalent circle diameter is 3.0 μm or less, and the sulfide number density is 0.050 pieces / μm 2 above.
[0040] 《Optional Elements》
[0041] The stainless steel of the present invention is composed of a chemical composition containing Fe and impurities in addition to the above-mentioned elements. Furthermore, in addition to the above-mentioned component composition, the following elements may be selectively contained in place of a part of Fe.
[0042] B can be contained as needed because it forms fine BN when contained together with N, thereby inhibiting the bonding of the base material on the tool surface and preventing the built-up edge on the cutting surface. However, if B is contained in excess of 0.01%, coarse borides are generated, which deteriorates the life of the cutting tool and promotes the formation of built-up edge. Therefore, the B content is limited to less than 0.01%. In order to reliably obtain the above-mentioned effect, it is preferred to set the B content to 0.002% to 0.007%.
[0043] N can be contained as needed because it not only forms fine BN to prevent built-up edge marks on the cutting surface, but also increases the hardness of the base material after quenching. However, if N exceeds 0.15%, coarse nitrides are formed, which deteriorates the life of the cutting tool. Therefore, the N content is set to 0.15% or less. In order to reliably obtain the above-mentioned effect, it is preferred to set the N content to 0.03% to 0.10%.
[0044] Al may be contained for deoxidation, but if contained in excess of 0.008%, coarse inclusions are generated and the life of the cutting tool is deteriorated. Therefore, the Al content is limited to 0.008% or less, preferably 0.006% or less.
[0045] O is mixed in as an inevitable impurity, but if it is contained in excess of 0.015%, coarse inclusions are generated and the life of the cutting tool is deteriorated. Therefore, the O content is limited to 0.015% or less, preferably 0.012% or less.
[0046] Ni, Cu or Co can be contained as needed because they improve the corrosion resistance and toughness of the product. However, if each element is contained in an amount exceeding 1.5%, the life of the cutting tool will be deteriorated. Therefore, the content of each element is limited to 1.5% or less. In order to reliably obtain the above-mentioned effects, it is preferred that the content of each element be set to 0.01% to 1.0%.
[0047] Mo and W can be contained as needed to improve the corrosion resistance of the product. However, if more than 2.5% is contained, the effect is saturated and the life of the cutting tool is deteriorated. Therefore, the content of each element is limited to 2.5% or less. In order to reliably obtain the above-mentioned effect, it is preferred to set the content of each element to 0.01% to 2.0%.
[0048] Bi can be contained as needed because it has a self-lubricating effect during cutting, inhibits the formation of built-up edge and improves the cutting surface properties. However, if it contains more than 0.2%, the hot manufacturing properties will deteriorate significantly and it will become impossible to manufacture. Therefore, the Bi content is limited to 0.2% or less. In order to reliably obtain the above-mentioned effect, it is preferred to set the Bi content to 0.005% to 0.10%.
[0049] Sn, Sb or Ag can be contained as needed because they play a self-lubricating role during cutting, inhibit the formation of built-up edge and improve the cutting surface properties. However, if more than 0.3% is contained, the hot manufacturing property will be significantly deteriorated and it will become impossible to manufacture. Therefore, the content of each element is limited to less than 0.3%. In order to reliably obtain the above-mentioned effect, it is preferred to set the content of each element to 0.005% to 0.20%.
[0050] Te can be contained as needed because it generates spherical sulfides, inhibits the stacking and growth of built-up edges, and improves the cutting surface properties. However, if it contains more than 0.1%, the hot manufacturing properties will deteriorate significantly and it will become impossible to manufacture. Therefore, the Te content is limited to 0.1% or less. In order to reliably obtain the above-mentioned effect, it is preferred to set the Te content to 0.005% to 0.05%.
[0051] V can be contained as needed to improve the corrosion resistance of the product. However, if it exceeds 0.8%, coarse carbonitrides are formed, which deteriorates the life of the cutting tool. Therefore, the V content is limited to 0.8% or less. In order to reliably obtain the above effect, it is preferred to set the V content to 0.05% to 0.5%.
[0052] Nb, Ti or Ta can also be contained as needed because they improve the corrosion resistance of the product. However, if each is contained in an amount exceeding 0.3%, coarse carbonitrides are formed, which deteriorates the life of the cutting tool. Therefore, the content of each element is limited to 0.3% or less. In order to reliably obtain the above-mentioned effects, it is preferred that the content of each element be set to 0.01% to 0.2%.
[0053] Mg, Ca or Hf can also be contained as needed because they have the effect of improving hot manufacturability. However, even if more than 0.01% is contained, the effect is saturated, and coarse oxides are generated, which deteriorates the life of the cutting tool. Therefore, the content of each element is limited to 0.01% or less. In order to reliably obtain the above-mentioned effect, it is preferred to set the content of each element to 0.001% to 0.005%.
[0054] Since REM has the effect of improving hot manufacturability, it can also be contained as needed. However, even if REM is contained in excess of 0.05%, its effect is saturated, and coarse oxides are generated, which deteriorates the life of the cutting tool. Therefore, the REM content is limited to less than 0.05%. In order to reliably obtain the above-mentioned effect, it is preferred to set the REM content to 0.001% to 0.005%. According to the general definition, REM (rare earth elements) refers to the general term for two elements of scandium (Sc) and yttrium (Y) and 15 elements (lanthanide elements) from lanthanum (La) to lutetium (Lu). It can be contained alone or as a mixture.
[0055] Impurities contained in the stainless steel of the present invention include Zn, Pb, Ge, Se, and the like as typical impurities, which are usually mixed in the range of about 0.1% as impurities in the steel production process.
[0056] Oxygen as an impurity exists in steel mainly as inclusions, but the oxygen content level of stainless steel produced by ordinary refining is 0.001 to 0.015%.
[0057] In addition, with regard to the optionally contained elements, representative elements are specified in the above (3), but even elements not described in this specification may be contained within a range that does not impair the effects of the present invention.
[0058] 《Cr carbide control method》
[0059] The Cr carbide control method of the present invention will be described.
[0060] In order to make the average Cr carbide equivalent circle diameter less than 0.80 μm and the Cr carbide number density less than 0.10 pieces / μm 2 The fine dispersion is carried out as above, and preferably, hot working such as hot rolling with a finishing rolling temperature of 800 to 1150°C is carried out, and after the hot working, intermittent annealing is carried out by holding at 700 to 900°C for 60 to 300 minutes and cooling to 600°C at a rate of 20 to 200°C / h. In addition, it is preferred that wire annealing is carried out by holding at 700 to 850°C for 30 to 1000 seconds on the basis of intermittent annealing under the same conditions as above. This range of manufacturing conditions is referred to as a preferred range.
[0061] When the hot working finishing temperature is lower than 800°C, the rolling load becomes high, so the manufacturability is reduced. On the other hand, if the finishing temperature exceeds 1150°C, the Cr carbide coarsens and the above-mentioned average Cr carbide equivalent circle diameter condition is not satisfied. Therefore, the hot working finishing temperature is set to 800-1150°C.
[0062] In the intermittent annealing performed after hot working, if the intermittent annealing temperature is lower than 700°C and the holding time of the intermittent annealing is shorter than 60 minutes, the annealing is insufficient and the manufacturability is reduced. On the other hand, if the intermittent annealing temperature is higher than 900°C, the holding time of the intermittent annealing is longer than 300 minutes, and the cooling rate from the end of the holding to 600°C is slower than 20°C / h, the Cr carbide coarsens and the above-mentioned equivalent circle diameter is not satisfied. It should be noted that if the cooling rate is faster than 200°C / h, hardening occurs due to the martensitic phase transformation, and delayed fracture becomes easy to occur. There is no need to specifically limit the cooling rate below 600°C.
[0063] When wire annealing is performed on the basis of intermittent annealing after hot working, the intermittent annealing conditions are the same as the intermittent annealing conditions described above. For wire annealing, if the wire annealing temperature is lower than 700°C and the wire annealing holding time is shorter than 30 seconds, the annealing is insufficient and the manufacturability is reduced. On the other hand, if the wire annealing temperature is higher than 850°C and the wire annealing holding time is longer than 1000 seconds, not only will the above-mentioned equivalent circle diameter not be satisfied due to the coarsening of Cr carbides, but also hardening occurs due to martensitic transformation when cooling beyond the Ac1 point, making it easy to cause delayed fracture, etc.
[0064] As described above, the finishing rolling temperature of hot working is limited to 800-1150°C, the intermittent annealing conditions are limited to maintaining at 700-900°C for 60-300 minutes and the cooling rate to 600°C is 20-200°C / h, and the wire annealing conditions are limited to maintaining at 700-850°C for 30-1000 seconds.
[0065] In the above preferred range, the lower the finishing temperature becomes, the lower the intermittent annealing temperature becomes, the shorter the holding time becomes, the faster the cooling rate after holding becomes, and the lower the wire annealing temperature becomes, the shorter the holding time becomes, the lower the average Cr carbide equivalent circle diameter becomes, and the higher the Cr carbide number density becomes. Therefore, by adjusting the manufacturing conditions within the above preferred range based on this tendency, it is possible to reliably achieve an average Cr carbide equivalent circle diameter of 0.80 μm or less and a Cr carbide number density of 0.10 / μm. 2 The above is finely dispersed.
[0066] It should be noted that when finely dispersing Cr carbides, the finishing temperature is preferably lower than 1000°C, and more preferably lower than 900°C. As a preferred range, the finishing temperature is above 850°C and lower than 900°C, the intermittent annealing conditions are to maintain at 750-850°C for 90-200 minutes, and the cooling rate after maintaining until 600°C is 30-100°C / h, and the wire annealing conditions are to maintain at 750-825°C for 40-800 seconds. By manufacturing within the range of this condition, it is possible to reliably achieve the average Cr carbide equivalent circle diameter of less than 0.80μm and the Cr carbide number density of 0.10 pieces / μm. 2 The above method is used for fine dispersion.
[0067] In addition, wire annealing refers to the following annealing method: a wire or steel wire coil wound into a ring is unrolled into a straight line and heat-treated in a straight state for a short time (in an atmosphere of nitrogen, Ar or ammonia decomposition gas, etc.), and air-cooled or indirectly water-cooled. Compared with intermittent annealing of the entire ring coil, the cooling rate can be significantly accelerated.
[0068] 《Sulfide Control Methods》
[0069] Next, the sulfide control method will be described.
[0070] In order to make the average sulfide equivalent circle diameter less than 5.0 μm and the sulfide number density less than 0.010 pieces / μm 2The above method is used to finely disperse the sulphide. After the hot working such as hot rolling and annealing described in the above-mentioned "Cr carbide control method", cold working such as cold drawing with a cross-sectional reduction rate of 20.0 to 99.0% is performed. Sulfide is elongated after hot rolling and annealing, but the sulfide is cut and finely dispersed by cold working such as cold drawing. Therefore, the cross-sectional reduction rate is set to 20.0% or more. However, if the cross-sectional reduction rate exceeds 99.0%, the manufacturability is reduced due to the embrittlement of the base material, so the cross-sectional reduction rate is limited to 99.0% or less. The preferred cross-sectional reduction rate is 30.0 to 90.0%.
[0071] It should be noted that if the cross-sectional shrinkage of cold working such as cold drawing becomes as high as about 70% or more, defects such as shrinkage cracks may occur due to work hardening. In order to prevent this defect, cold working such as cold drawing and annealing may be repeatedly performed multiple times. In this case, the annealing performed between cold working and cold working needs to be performed under the annealing conditions described in the above-mentioned "Cr Carbide Control Method" in order to control Cr carbides. In addition, the above-mentioned cross-sectional shrinkage of cold working such as cold drawing is the sum of the cross-sectional shrinkage of each cold working performed multiple times.
[0072] According to the present invention described above, it is possible to provide a martensitic free-machining stainless steel bar material for high-hardness parts to be precisely machined, which has excellent tool life during cutting and excellent cut surface properties.
[0073] It should be noted that the martensitic stainless steel in the present invention refers to steel that is hardened by martensitic transformation during quenching. In the present invention, for example, it refers to steel in which more than 70% of the metal structure shows a martensitic structure when quenched by air cooling from 1050°C and hardened to 400Hv or more.
[0074] In the present invention, the rod-shaped steel material refers to a concept including "steel bar", "rod wire", "wire rod", "steel wire", "special-shaped wire", and "special-shaped steel bar".
[0075] Example
[0076] <Example 1>
[0077] In order to investigate the influence of the composition, the steels with the chemical compositions shown in Tables 1 to 3 were melted at 1600°C in a 45kg vacuum melting furnace and cast into a mold. After that, after heating at 1200°C, hot rolling was performed at a finishing temperature of 880°C to form a φ5.5mm wire rod, which was then cooled to room temperature. After that, intermittent annealing was performed under the conditions of an annealing temperature of 850°C, a holding time of 180 minutes, and a cooling rate of 50°C / h until 600°C after holding. After intermittent annealing, cold working was performed with a cross-sectional reduction rate of 66.1% for cold drawing, and the wire rod was set to φ3.2mm. After that, it was finished into a φ3.0mm grinding rod (rod wire) by straightening and centerless grinding as a raw material for cutting.
[0078] [Table 1]
[0079]
[0080] [Table 2]
[0081]
[0082] [Table 3]
[0083]
[0084] The underline indicates that the content is outside the range specified in the present invention.
[0085] The rods and wires thus obtained were evaluated by the following evaluation methods for average Cr carbide equivalent circle diameter, Cr carbide number density (number per unit area), average sulfide equivalent circle diameter, sulfide number density, tool life after peripheral cutting, and surface properties. The results are shown in Tables 4 to 6. Tables 4 and 5 show the evaluation results of the examples of the present invention, and Table 6 shows the evaluation results of the comparative examples.
[0086] The quenching hardness is evaluated by quenching at 1050°C through air cooling, and 400Hv and above are set as good. The corrosion resistance is evaluated by implementing a 48-hour acetic acid salt water spray test, and the case where no rusting occurs is set as good. In the case where either the quenching hardness or the corrosion resistance deviates from the good standard, it is recorded in the remarks as "poor quenching hardness" or "poor corrosion resistance", and no other evaluation is performed. In addition, if it cannot be manufactured for some reason, it is recorded as "cannot be manufactured" and no quality evaluation is performed.
[0087] [Table 4]
[0088]
[0089] [Table 5]
[0090]
[0091] [Table 6]
[0092]
[0093] The underline indicates that the content is outside the range specified in the present invention.
[0094] "Average Cr carbide equivalent circle diameter and Cr carbide number density"
[0095] The sample was embedded in resin so that the longitudinal cross section of the rod wire became the inspection surface. The inspection surface was mirror-polished and then etched with aqua regia. The 100 μm 2 Observe 5 fields of view over an area of 500 square meters. Inclusions in the field of view in which Cr and C are detected more by EDX analysis are identified as Cr carbides. The average Cr carbide equivalent circle diameter is obtained by calculating the equivalent circle diameter of more than 100 Cr carbides and averaging their equivalent circle diameters. The Cr carbide number density is the total number of Cr carbides measured in 5 fields of view, converted into 1 μm 2 It can be calculated by the number of Cr carbides.
[0096] “Average sulfide equivalent circle diameter and sulfide number density”
[0097] The sample was embedded in the resin so that the longitudinal section of the rod wire became the inspection surface. After the inspection surface was mirror-polished, a 3 mm 2 Observe 5 fields of view over an area of 500 square meters. Inclusions in the field of view in which S is detected more by EDX analysis are identified as sulfides. The average sulfide equivalent circle diameter is calculated by averaging the equivalent circle diameters of more than 100 sulfides. The sulfide number density is the total number of sulfides measured in 5 fields of view, converted into 1 μm 2 The number of sulfides can be used to calculate.
[0098] “Cutting tool life”
[0099] The outer circumference of the rod wire was cut in the circumferential direction for 1 hour under the following precision cutting conditions: Tool used: superhard P type, blade tip R0.03mm, cutting speed: 20m / min, feed rate: 0.01mm / rev, cutting depth: 0.1mm, cutting oil (mineral oil): yes. The tool after cutting was observed under an optical microscope at 200 times. If the boundary wear width of the tool after cutting was less than 100μm, it was evaluated as "S", if it was more than 100μm and less than 200μm, it was evaluated as "G", and if it was more than 200μm, it was evaluated as "X".
[0100] “Cutting surface properties”
[0101] The outer circumference of the rod and wire was cut for 1 hour in the circumferential direction under the following precision cutting conditions: tool used: superhard P type, tool tip R0.03 mm, cutting speed: 20 m / min, feed rate: 0.01 mm / rev, cutting depth: 0.1 mm, cutting oil (mineral oil): available. The surface of the rod and wire after cutting was observed with an optical microscope at 100 times magnification. The case where clear built-up edge marks were confirmed on the surface was evaluated as "X", the case where fine built-up edge marks were sparsely observed was evaluated as "G", and the case where no clear built-up edge marks were confirmed was evaluated as "S".
[0102] The average Cr carbide equivalent circle diameter of Examples 1 to 57 of the present invention in Tables 4 to 5 is 0.80 μm or less, and the number density of Cr carbides is 0.10 pieces / μm 2 The average sulfide equivalent circle diameter is less than 5.0 μm, and the sulfide number density is 0.010 pieces / μm 2 All of the above show excellent cutting tool life and cutting surface properties.
[0103] On the other hand, Comparative Examples 1 to 33 in Table 6 are out of the composition range of the present invention and cannot satisfy all of the requirements for excellent cutting tool life and cutting surface properties. It should be noted that even when the average sulfide equivalent circle diameter and sulfide number density are within the preferred ranges, the cutting surface properties deteriorate in accordance with the deterioration of the cutting tool life.
[0104] <Example 2>
[0105] In order to evaluate the influence of the manufacturing process, the steel with the chemical composition shown in Steel C of Table 1 was melted at 1600°C in a 45kg vacuum melting furnace and cast into a mold. The manufacturing conditions are shown in Table 7. As hot working, after heating at 1200°C, hot rolling was performed at a finishing rolling temperature of 760-1170°C to produce a wire rod of φ5.5-40.0 mm, and then cooled to room temperature. Thereafter, a separate intermittent annealing was performed, or wire rod annealing was performed on the basis of intermittent annealing. For intermittent annealing, the annealing temperature was set to 650-950°C, the holding time was 40-360 minutes, and the cooling rate after holding until 600°C was set to a range of 10-250°C / h. For wire rod annealing (in ammonia decomposition gas), the annealing temperature was set to 680-870°C and the holding time was set to 20-1200 seconds. After annealing, for the examples 59 to 67 of the present invention and the comparative examples 34 to 45 in Table 7, cold drawing was performed at a cross-sectional reduction rate of 19.0 to 99.4%, and then the rods (rods and wires) with a diameter of 3.0 mm were finished by straightening and centerless grinding, and used as raw materials for cutting. In the case where the cross-sectional reduction rate is high and the work hardening is large, annealing and wire drawing are repeated to produce. For the example 58 of the present invention, a wire rod with a diameter of 5.5 was used and cold drawing was not performed. The rods (rods and wires) with a diameter of 3.0 mm were finished by centerless grinding, and used as raw materials for cutting. Thereafter, the average Cr carbide equivalent circle diameter, Cr carbide number density, average sulfide equivalent circle diameter, sulfide number density, tool life after peripheral cutting, and surface properties were evaluated by the same evaluation method as in the above-mentioned Example 1. The results are shown in Table 7.
[0106] [Table 7]
[0107]
[0108] The average Cr carbide equivalent circle diameter of Inventive Examples 58 and 59 in Table 7 was 0.80 μm or less, and the number density of Cr carbides was 0.10 pieces / μm 2 As described above, excellent cutting tool life is shown. It should be noted that, since cold drawing was not performed in Example 58 of the present invention, and since the wire drawing cross-sectional reduction ratio of cold drawing was out of the lower limit of the preferred range of the present invention in Example 59 of the present invention, as a result, the average sulfide equivalent circle diameter and sulfide number density were out of the preferred range, and excellent cutting surface properties could not be satisfied.
[0109] The average Cr carbide equivalent circle diameter of Examples 60 to 67 of the present invention in Table 7 is 0.80 μm or less, and the number density of Cr carbides is 0.10 pieces / μm 2 The average sulfide equivalent circle diameter is less than 5.0 μm, and the sulfide number density is 0.010 pieces / μm 2 All of the above show excellent cutting tool life and excellent cutting surface properties.
[0110] On the other hand, the manufacturing conditions of Comparative Examples 34 to 45 in Table 7 deviate from the preferred conditions of the present invention and cannot be manufactured, or even if they can be manufactured, the average Cr carbide equivalent circle diameter and Cr carbide number density are out of the range of the present invention. As a result, both excellent cutting tool life and cutting surface properties cannot be satisfied. In addition, the wire drawing reduction ratio of Comparative Example 46 deviates from the upper limit of the preferred range of the present invention and cannot be manufactured.
[0111] Industrial Applicability
[0112] As shown in the above embodiments, the present invention can provide a martensitic free-cutting stainless steel having excellent tool life during precision cutting and preferably excellent cutting surface properties, and can greatly improve the durability of high-hardness parts used in environments with severe corrosion and requiring fatigue strength and wear resistance, which is extremely useful in industry.
Claims
1. A martensitic free-cutting stainless steel bar material, characterized in that: It has the following chemical composition: in mass %, C:0.10~0.60%、 Si: 0.1-2.0%, Mn: 0.1-3.0%, S:0.15~0.40%、 P: 0.10% or less, Cr:11.0~16.0%、 The rest contains Fe and impurities. The average Cr carbide equivalent circle diameter is less than 0.80μm, and the number density of Cr carbides is 0.10 / μm 2 above.
2. A martensitic free-cutting stainless steel bar material, characterized in that: It has the following chemical composition: in mass %, C:0.10~0.60%、 Si: 0.1-2.0%, Mn: 0.1-3.0%, S:0.15~0.40%、 P: 0.10% or less, Cr:11.0~16.0%、 The rest contains Fe and impurities. The average Cr carbide equivalent circle diameter is less than 0.80μm, and the number density of Cr carbides is 0.10 / μm 2 The average sulfide equivalent circle diameter is less than 5.0 μm, and the sulfide number density is 0.010 pieces / μm 2 above.
3. The martensitic free-cutting stainless steel bar material according to claim 1 or claim 2, characterized in that: The chemical composition of the steel contains, in mass %, one or more selected from the following elements in place of a portion of the Fe: B: 0.01% or less, N: 0.15% or less, Al: 0.008% or less, O: 0.015% or less, Ni: 1.5% or less, Cu: 1.5% or less, Co: 1.5% or less, Mo: 2.5% or less, W: 2.5% or less, Bi: 0.2% or less, Sn: 0.3% or less, Sb: 0.3% or less, Ag: 0.3% or less, Te: 0.1% or less, V: 0.8% or less, Nb: 0.3% or less, Ti: 0.3% or less, Ta: 0.3% or less, Mg: 0.01% or less, Ca: 0.01% or less, Hf: 0.01% or less, and REM: 0.05% or less.
4. The method for producing a martensitic free-cutting stainless steel bar according to claim 1 or claim 2, characterized in that: The finishing rolling temperature of hot working is 800-1150°C, and after hot working, intermittent annealing is performed by maintaining the temperature at 700-900°C for 60-300 minutes and cooling to 600°C at a rate of 20-200°C / h, or wire annealing is performed on the basis of the intermittent annealing by maintaining the temperature at 700-850°C for 30-1000 seconds.
5. The method for manufacturing a martensitic free-cutting stainless steel bar according to claim 4, characterized in that: Further, cold working is performed with a cross-sectional reduction rate of 20.0 to 99.0%.
6. The method for producing a martensitic free-cutting stainless steel bar according to claim 3, characterized in that: The finishing rolling temperature of hot working is 800-1150°C, and after hot working, intermittent annealing is performed by maintaining the temperature at 700-900°C for 60-300 minutes and cooling to 600°C at a rate of 20-200°C / h, or wire annealing is performed on the basis of the intermittent annealing by maintaining the temperature at 700-850°C for 30-1000 seconds.
7. The method for manufacturing a martensitic free-cutting stainless steel bar according to claim 6, characterized in that: Further, cold working is performed with a cross-sectional reduction rate of 20.0 to 99.0%.
Citation Information
Patent Citations
Cold working tool steel
JP2006193790A
Free-cutting martensitic stainless steel rod wire and method for producing the same
JP2013185195A
Stainless steel having excellent machinability, hardness, abrasion resistance and corrosion resistance
JP2015137381A
Martensitic s free-cutting stainless steel
WO2019240209A1